A comparative analysis of 3D bioprinted gelatin-hyaluronic acid-alginate scaffold and microfracture for the management of osteochondral defects in the rabbit knee joint - Aydin, Mahmud; Ok, Mesut; Cerci, Mehmet Halis; Demirhan, Ramazan; Surucu, Serkan; Mahirogullari, Mahir (TURKISH JOINT DISEASES FOUNDATION, 2024)
Objectives: This study aims to compare the radiological, biomechanical, and histopathological results of microfracture treatment and osteochondral damage repair treatment with a new scaffold product produced by the three-dimensional (3D) bioprinting method containing gelatin-hyaluronic acid-alginate in rabbits with osteochondral damage. Materials and methods: A new 3D bioprinted scaffold consisting of gelatin, hyaluronic acid, and alginate designed by us was implanted into the osteochondral defect created in the femoral trochlea of 10 rabbits. By randomization, it was determined which side of 10 rabbits would be repaired with a 3D bioprinted scaffold, and microfracture treatment was applied to the other knees of the rabbits. After six months of follow-up, the rabbits were sacrificed. The results of both treatment groups were compared radiologically, biomechanically, and histopathologically. Results: None of the rabbits experienced any complications. The magnetic resonance imaging evaluation showed that all osteochondral defect areas were integrated with healthy cartilage in both groups. There was no significant difference between the groups in the biomechanical load test (p=0.579). No statistically significant difference was detected in the histological examination using the modified Wakitani scores (p=0.731). Conclusion: Our study results showed that 3D bioprinted scaffolds exhibited comparable radiological, biomechanical, and histological properties to the conventional microfracture technique for osteochondral defect treatment.
Keywords: Bioprinted; histopathological; microfracture; osteochondral defect; scaffold; Wakitani score; REPAIR; Orthopedics; Surgery